2022
DOI: 10.1039/d2lc00393g
|View full text |Cite
|
Sign up to set email alerts
|

Microscope-based light gradient generation for quantitative growth studies of photosynthetic micro-organisms

Abstract: Photosynthetic micro-organisms are equipped with molecular machineries that are designed to transform light into chemical or bioenergy, and help shape and balance the ecosystem of all life forms on earth....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…We propose a general colimitation growth model for algal cells subjected to both physical and chemical parameters. Previous work in our labs showed that algal cell growth followed Monod growth kinetics when grown with either a nitrogen or a light intensity gradient alone 39 , 51 . Here, we hypothesized that algal growth response to light or nitrogen was described by Monod kinetics individually, and the synergistic effect of light and nitrogen on algal growth was reflected in a multiplicative term of the model: …”
Section: Resultsmentioning
confidence: 76%
See 4 more Smart Citations
“…We propose a general colimitation growth model for algal cells subjected to both physical and chemical parameters. Previous work in our labs showed that algal cell growth followed Monod growth kinetics when grown with either a nitrogen or a light intensity gradient alone 39 , 51 . Here, we hypothesized that algal growth response to light or nitrogen was described by Monod kinetics individually, and the synergistic effect of light and nitrogen on algal growth was reflected in a multiplicative term of the model: …”
Section: Resultsmentioning
confidence: 76%
“…1 A and Ref. 51 ). Briefly, the light intensity gradient at the location of the array microhabitat was created by placing a half-moon shaped mask directly below the field iris of an Olympus IX81 microscope.…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations